An evaluation of the guidance program of the public secondary schools of Manila - Baltazar, Remedios Bautista (Colendrino) 1912- (University of the Philippines], 1953)
An evaluation of the guidance program that existed in the public secondary schools of Manila is in order. This study involves the present status of guidance work, problem areas covered by this program of guidance, the phases of the guidance that are taken cared of in the present set-up, the appointed guidance counselors, the techniques being used to carry out a guidance program, the criteria used to evaluate the set-up and the recommendations to improve the present set-up.